A peptide-based bio-metal-organic framework piezoelectric material and a synthesis method and application thereof, and a triboelectric / piezoelectric hybrid nanogenerator device and an assembling method and application thereof

CN118994615BActive Publication Date: 2026-10-16ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411084762.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2026-10-16
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

[0005]然而,受材料和结构设备的影响,目前报道的纳米发电机设备难以满足高稳定性、高输出性能和宽检测限的自供电传感器的需求

Benefits of technology

[0031] The method for synthesizing peptide-based biometal-organic framework piezoelectric materials provided by this invention uses safe raw materials. Using bio-derived small molecules L-carnosine and zinc ions as the backbone, a non-precious metal, renewable, and environmentally friendly piezoelectric Bio-MOF is prepared through functional design, and it also has degradability and biosafety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994615B_ABST
    Figure CN118994615B_ABST
Patent Text Reader

Abstract

The application discloses a kind of synthesis methods of peptide-based biological metal organic framework piezoelectric material: after heating, Zn-Car_MOF material is obtained by adding zinc nitrate hexahydrate and L-muscle peptide into solvent;The application also discloses the piezoelectric material obtained by the above method and its application in triboelectric / piezoelectric hybrid nanogenerator device.The application also discloses a kind of assembly methods of triboelectric / piezoelectric hybrid nanogenerator device: the above-mentioned Zn-Car_MOF material is added to patterned PDMS to construct triboelectric / piezoelectric hybrid nanogenerator device;The application also discloses the nanogenerator device obtained by the above-mentioned assembly method and its application in environmental energy collection and gait monitoring.The Zn-Car_MOF material provided by the application has good piezoelectric performance and degradability, the nanogenerator device provided by the application has wide range of pressure responsiveness, high sensitivity and stability in various environments, can effectively collect free mechanical energy in various environments and be applied to motion monitoring and gait sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of biotechnology and piezoelectric materials technology, specifically relating to a peptide-based biometal-organic framework piezoelectric material and its synthesis method and application, and a triboelectric / piezoelectric hybrid nanogenerator device and its assembly method and application. Background Technology

[0002] In recent years, with rapid economic development and the increasing energy demand for lightweight medical devices, the need for new lightweight, renewable, and continuously powered devices has become increasingly urgent. Currently, miniature portable medical devices powered by dry cell batteries are ubiquitous in our daily lives. However, the environmental pollution caused by these batteries, which are based on heavy metals and rare earth elements, is a significant problem. Currently, most environmental kinetic energy, such as wind, tidal, and rainwater energy, is converted into electrical energy through turbine generators, which suffer from complex and bulky equipment and insufficient sensitivity, making them difficult to apply in portable devices. Therefore, developing environmentally friendly materials and new portable power supply devices that can utilize widely renewable environmental kinetic energy to achieve highly sensitive and broad-spectrum energy harvesting is of great significance.

[0003] Among novel materials, metal-organic frameworks (MOFs) are self-assembled from a central metal and organic ligands, forming crystalline organic-inorganic hybrid materials with a periodic network structure. As a novel porous material, MOFs possess characteristics such as large specific surface area, high porosity, controllable structure, and biodegradability. Recently, bio-MOFs based on biomolecules and non-noble metal ions have shown broad application potential in addressing environmental issues due to their low toxicity, good biocompatibility, and environmental sustainability. Furthermore, novel functional MOFs (such as piezoelectric MOFs) have demonstrated great application prospects in environmental energy harvesting and energy supply. For example, Chinese patent CN116425997A discloses a metal-organic framework material and its ligands, and their application in triboelectric nanogenerators. This material is abbreviated as MOF ET10, with the chemical formula [Zn₂CoL], where L represents C. 60 H 37 NO 12 The preparation method of the above metal-organic framework material is as follows: a mixed solution of Zn(NO3)2·6H2O, ligand, and N,N-dimethylformamide nitric acid is placed in a reaction vessel, the mixture is sealed, and heated at 120°C for 72 h to obtain colorless crystals. Then, the colorless crystals are added to an N,N-dimethylformamide solution containing Co(NO3)2, and then placed in a vacuum drying oven at 50°C for 36 h to obtain pink crystals, which is MOF ET10.

[0004] Free kinetic energy in the environment, as a widely existing and diverse form of energy, is a green energy source with broad application prospects. Mechanical nanogenerators (MNGs) developed in recent years, such as triboelectric nanogenerators (TENGs) and piezoelectric nanogenerators (PENGs), can convert mechanical energy into electrical energy, offering advantages such as high performance, ease of design and manufacturing, and light weight. However, using single triboelectric and piezoelectric devices suffers from limitations in application scope, low sensitivity, and low efficiency. Therefore, scientists have proposed a hybrid strategy based on the triboelectric / piezoelectric effects of TENGs and PENGs. When the triboelectric / piezoelectric hybrid nanogenerator (TPHG) is subjected to mechanical stress, the surface charge from the triboelectric effect and the polarization charge from the piezoelectric effect combine, improving the surface charge density and output performance. TPHG devices exhibit excellent performance and demonstrate significant potential for efficient energy harvesting and self-powered sensing in various smart applications, such as environmental energy harvesting systems and wearable monitoring devices.

[0005] However, due to limitations in materials and structural design, currently reported nanogenerator devices struggle to meet the demands of self-powered sensors requiring high stability, high output performance, and wide detection limits. Furthermore, current nanogenerator devices are structurally and functionally constrained, making them unsuitable for various application scenarios (rain, tides, and motion). MOF materials, due to their unique organic conjugated structure, have been found to possess piezoelectric nanogenerator output performance. When combined with polymer triboelectric materials such as polydimethylsiloxane (PDMS), even higher surface charge density and output performance can be achieved. Therefore, it is necessary to synthesize new MOF materials with excellent output performance and cycling stability, and to develop TPHG devices with high sensitivity, wide detection limits, good stability, broad flexibility, and durability through patterned design of triboelectric polymers. Summary of the Invention

[0006] The purpose of this invention is to provide a peptide-based biometal-organic framework piezoelectric material with good piezoelectric properties and biodegradability. This invention also provides a triboelectric / piezoelectric hybrid nanogenerator device suitable for environmental energy harvesting and gait monitoring.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] A method for synthesizing a peptide-based biometal-organic framework piezoelectric material, the method comprising: adding zinc nitrate hexahydrate and L-carnosine to a solvent and heating to obtain a Zn-Car_MOF material.

[0009] In this invention, the Zn-Car_MOF material is also referred to as peptide-based Bio-MOF piezoelectric material.

[0010] The Zn-Car_MOF synthesized in this invention is a type of Bio-MOF material with piezoelectric properties. It can undergo directional polarization under stress to generate polarization charge, thus generating output voltage and current. Furthermore, it can autodegrade in acidic environments.

[0011] Preferably, the molar ratio of zinc nitrate hexahydrate to L-carnosine is 1:1-2:1. During the synthesis of Zn-Car, the feed ratio of the raw materials can control the morphological characteristics of the product: as the molar ratio of zinc nitrate hexahydrate to L-carnosine decreases, the synthesized Zn-Car material gradually transforms from micron-sized plate-like elongated prisms to nano-sized plate-like crystal stacked spherical particles, thus improving the piezoelectric properties of the synthesized Zn-Car_MOF material.

[0012] Preferably, in the synthesis of Zn-Car_MOF, the solvent used is a DMF / H2O mixed organic solvent with a volume ratio of 2:1.

[0013] Preferably, the heating temperature is 80-150℃. As the temperature increases, the stacking of nanoscale plate-like crystals on the surface of the synthesized Zn-Car particles becomes denser, and the piezoelectric properties of the Zn-Car piezoelectric material are also improved.

[0014] More preferably, the mixture is continuously heated in an oven at 100°C for 12 hours to obtain Zn-Car_MOF material.

[0015] Preferably, in the synthesis of Zn-Car_MOF, the Zn-Car obtained by the hydrothermal method needs to be filtered, washed, and dried. The washing agents used for filtration and washing include, but are not limited to, ethanol and water. Then, the washed Zn-Car_MOF is dried in an oven to obtain Zn-Car_MOF powder.

[0016] The present invention also provides a peptide-based biometal-organic framework piezoelectric material obtained by the above-described synthesis method.

[0017] The peptide-based biometal-organic framework piezoelectric material is a regular sphere formed by the self-assembly of MOF nanoscale plate-like crystals with an average diameter of 4.2±0.8μm, an average length of 136.2±50.1nm, and an average width of 24.0±5.2nm.

[0018] Alternatively, the peptide-based biometal-organic framework piezoelectric material is self-assembled from plate-like crystals with an average length of 82±13.1μm and an average width of 8.2±0.8nm.

[0019] The present invention also provides an application of the above-mentioned peptide-based biometal-organic framework piezoelectric material in triboelectric / piezoelectric hybrid nanogenerator devices.

[0020] The present invention also provides a method for assembling a triboelectric / piezoelectric hybrid nanogenerator device, the method comprising: adding the above-mentioned peptide-based biometal-organic framework piezoelectric material into patterned PDMS to construct a triboelectric / piezoelectric hybrid nanogenerator device.

[0021] Triboelectric / piezoelectric hybrid nanogenerators constructed from Zn-Car MOF materials and patterned PDMS exhibit high sensitivity, wide detection limits, high stability, and broad flexibility / durability. Therefore, this invention constructs a flexible triboelectric / piezoelectric hybrid nanogenerator device by combining Zn-Car MOF materials with patterned PDMS. This device can be used for broad-spectrum energy harvesting and human motion monitoring, providing a lightweight, renewable, and green energy supply solution for wearable devices.

[0022] The patterned PDMS is prepared by using a template method to obtain a patterned PDMS film via a mold. Specifically, prepolymer A (main component is polydimethoxysilane) and crosslinking agent B (prepolymer with vinyl side chains) are uniformly mixed in a 10:1 ratio; the PDMS is then cured in an oven at 60°C for 6 hours using an epoxy resin template.

[0023] Preferably, the area of ​​the micropillar array constructed by the template method, with a surface diameter of 1 mm and a height of 0.5-1 mm, is 2 × 2 cm². 2 The PDMS film has a distance of 1 mm between each micropillar.

[0024] The addition amount of the Zn-Car_MOF material meets the following requirement: 0.1 mg / cm³ 2 The amount of Zn-Car-MOF material added is ≤5 mg / cm³. 2 The amount of Zn-Car powder added affects the overall piezoelectric properties of the device. Excessive addition (>20mg, 2×2cm) can negatively impact the piezoelectric performance. 2 When using PDMS thin films, the reduced porosity of Zn-Car powder will decrease the output performance during friction and extrusion.

[0025] More preferably, 20 mg of Zn-Car powder is added to an area of ​​2 × 2 cm². 2 Between patterned PDMS and unpatterned PDMS films.

[0026] The assembly method includes: adding peptide-based bio-metal-organic framework piezoelectric material to the space between patterned PDMS and unpatterned PDMS films in the triboelectric / piezoelectric hybrid nanogenerator device, and separating them with tape; attaching aluminum foil and copper conductive tape as electrodes to the outer layers of both patterned and unpatterned PDMS films, and encapsulating them with PI film.

[0027] Preferably, the patterned PDMS film and the unpatterned PDMS film are 3mm thick, with a 1mm thick double-sided tape as a spacer in between; aluminum foil and copper tape are added to the back of the PDMS layer as electrodes, and the outermost layer is encapsulated with polyimide tape to ensure its sealing and waterproof properties.

[0028] The present invention also provides a triboelectric / piezoelectric hybrid nanogenerator device obtained by the above assembly method. That is, a triboelectric / piezoelectric hybrid nanogenerator device synergistically constructed from peptide-based Bio-MOF piezoelectric material and patterned PDMS.

[0029] This invention also provides applications of the above-mentioned triboelectric / piezoelectric hybrid nanogenerator device in environmental energy harvesting and gait monitoring.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The method for synthesizing peptide-based biometal-organic framework piezoelectric materials provided by this invention uses safe raw materials. Using bio-derived small molecules L-carnosine and zinc ions as the backbone, a non-precious metal, renewable, and environmentally friendly piezoelectric Bio-MOF is prepared through functional design, and it also has degradability and biosafety.

[0032] The triboelectric / piezoelectric hybrid nanogenerator device constructed by the present invention using Zn-Car piezoelectric MOF and patterned PDMS has high sensitivity, high output performance, high stability and wide pressure range response, and has considerable flexibility, which can withstand complex deformations such as bending, extrusion and torsion.

[0033] The triboelectric / piezoelectric hybrid nanogenerator device prepared by this invention can be used for broad-spectrum environmental energy harvesting such as rainwater energy, ocean wave / tidal energy, and electric vehicle driving energy. It can also be used as a wearable device for human motion energy harvesting and motion monitoring, and can be used for gait disease monitoring and prevention. It provides a lightweight, renewable green energy supply wearable device solution. Attached Figure Description

[0034] Figure 1 This is a schematic diagram illustrating the synthesis principle of the Zn-Car_MOF piezoelectric material in Example 1.

[0035] Figure 2 This is a scanning electron microscope (SEM) image of the 1:1 Zn-Car_MOF piezoelectric material in Example 1.

[0036] Figure 3 This is a SEM image of the 2:1 Zn-Car_MOF piezoelectric material in Example 1.

[0037] Figure 4These are the X-ray diffraction (XRD) spectra of the 1:1 Zn-Car_MOF and the simulated Zn-Car_MOF single crystal in Example 1.

[0038] Figure 5 This is the nitrogen adsorption (BET) diagram and pore size distribution of the 1:1 Zn-Car_MOF in Example 1.

[0039] Figure 6 This is a Fourier transform infrared (FTIR) image of 1:1 Zn-Car_MOF and L-carnosine in Example 1.

[0040] Figure 7 This is the X-ray photoelectron spectroscopy (XPS) spectrum of the 1:1 Zn-Car_MOF in Example 1.

[0041] Figure 8 The piezoelectric response and piezoelectric coefficient (d) of the 1:1 Zn-Car_MOF in Example 1 are shown. 33 ).

[0042] Figure 9 This is an SEM image of the patterned PDMS surface morphology in Example 2.

[0043] Figure 10 This is a flexible test diagram of the Zn-Car_TPHG device in Example 2.

[0044] Figure 11 These are test images of the piezoelectric performance of the device before and after PDMS patterning in Example 2.

[0045] Figure 12 This is a test diagram of the piezoelectric performance of the TPHG device with 2:1 Zn-Car_MOF and 1:1 Zn-Car_MOF added in Example 2.

[0046] Figure 13 These are the output voltage and output current of the 1:1 Zn-Car_TPHG device in Example 2 under different external load conditions.

[0047] Figure 14 This refers to the output power density of the 1:1 Zn-Car_TPHG device in Example 2 under different external load conditions.

[0048] Figure 15 It is the open-circuit voltage of the 1:1 Zn-Car_TPHG device in Example 2 under different pressure conditions.

[0049] Figure 16 This refers to the cycle stability of the 1:1 Zn-Car_TPHG device in Example 2.

[0050] Figure 17It is 2×2cm in Example 2 2 Zn-Car_TPHG capacitor charging test diagram for raindrop energy harvesting.

[0051] Figure 18 It is 2×2cm in Example 2 2 Zn-Car_TPHG is the open-circuit voltage used for tidal energy harvesting.

[0052] Figure 19 It is the 10×10cm in Example 2 2 The open-circuit voltage of Zn-Car_TPHG at different speeds of the electric vehicle.

[0053] Figure 20 It is 2×2cm in Example 2 2 Zn-Car_TPHG is used for testing various motion state monitoring.

[0054] Figure 21 It is 2×2cm in Example 2 2 Zn-Car_TPHG is a test graph used for gait monitoring. Detailed Implementation

[0055] To make the objectives and technical solutions of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. The following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the field or in accordance with the product manual.

[0056] Example 1: Preparation of Zn-Car_MOF piezoelectric materials

[0057] Zn-Car piezoelectric materials were prepared using a solvothermal method. Carnosine powder and Zn(NO3)2·6H2O crystals were dissolved in water at concentrations of 80 mM and 160 mM, respectively. The carnosine solution (2 mL, 80 mM), Zn(NO3)2 solution (1 mL, 160 mM), solvent (10 mL DMF), and water (2 mL) were mixed in a 20 mL glass vial and subjected to vigorous sonication. The vial was heated to 100 °C at a rising rate of 1 °C / min and held for 12 h, then cooled to room temperature at a rate of 1 °C / min. The resulting crystals were washed three times with ethanol and deionized water, and then dried at 60 °C for 12 h. The product was collected in sample vials, with a yield of approximately 65%.

[0058] like Figure 1The diagram shown illustrates the synthesis principle of Zn-Car_MOF in Example 1. It describes the reaction of L-carnosine and Zn(NO3)2·6H2O under specific conditions to generate Zn-Car_MOF. DMF and H2O are used as solvents. Zn(II) forms a tetrahedral coordination with a carboxyl group, an amino terminal group, and two nitrogen atoms of the imidazole group on the carnosine molecule, forming a 4:4 basic structure.

[0059] like Figure 2 and Figure 3 The images shown are SEM images of 1:1 Zn-Car_MOF and 2:1 Zn-Car_MOF in Example 1, respectively: Figure 2 As shown, the 1:1 Zn-Car piezoelectric particles are regular spherical particles self-assembled from MOF nanoscale plate-like crystals with an average diameter of 4.2±0.8 μm, an average length of 136.2±50.1 nm, and an average width of 24.0±5.2 nm. Figure 3 As shown, 2:1 Zn-Car is a plate-like crystal with an average length of 82±13.1 μm and an average width of 8.2±0.8 nm. Among them, the piezoelectric properties of 1:1 Zn-Car_MOF are better than those of 2:1 Zn-Car_MOF.

[0060] like Figure 4 The image shows the XRD pattern of 1:1 Zn-Car_MOF in Example 1. The X-ray diffraction (XRD) pattern of Zn-Car_MOF shows multiple peaks at 10.5°, 12.0°, 12.6°, 19.8°, 20.8°, 21.1°, and 21.9°, which is very consistent with the simulated pattern of Zn-Car_MOF single crystal structure, indicating that Zn-Car_MOF was successfully synthesized.

[0061] like Figure 5 The image shows the BET adsorption diagram and pore size distribution of 1:1 Zn-Car_MOF in Example 1. Figure 5 The specific surface area, average pore size, and total pore volume of the 1:1 Zn-Car particles were 80.5 m². 2 ·g -1 9.57±0.04nm and 0.253cm 3 ·g -1 .

[0062] like Figure 6 The image shows the FTIR spectrum of a 1:1 Zn-Car MOF from Example 1. It can be observed that within the Zn-Car particles, at a depth of 3242 cm⁻¹... -1 The nearby peaks belong to the stretching vibrations of the NH bond and extend towards 3281 cm⁻¹. -1 Movement. Simultaneously, the tensile vibration peak of Zn-N appears at 1460 cm⁻¹.-1 The proximity of Zn and N was demonstrated, indicating coordination between them.

[0063] like Figure 7 The image shows the X-ray photoelectron spectrum of the 1:1 Zn-Car_MOF in Example 1. Characteristic peaks representing Zn, O, N, and C can be observed. Furthermore, Zn 2p... 1 / 2 There are two distinct characteristic peaks at 1044.8 eV and 1043.8 eV, Zn2p 3 / 2 The characteristic peaks at 1021.6 eV have a wide half-maximum width, which show the binding peaks of Zn-N at 1023.5 eV-1043.3 eV and the binding peaks of Zn-O at 1021.2 eV-1044 eV, respectively.

[0064] like Figure 8 As shown, the piezoelectric response and d of the 1:1 Zn-Car_MOF in Example 1 are illustrated. 33 Figure 1 shows that as the applied voltage increases, the piezoelectric signal of the Zn-Car_MOF gradually increases. The linear relationship between the voltage applied to the photodiode system and the planar piezoelectric response measured by PFM demonstrates that the Zn-Car crystal possesses significant piezoelectric properties. Specifically, the d1 of the 1:1 Zn-Car_MOF… 33 Piezoelectric coefficient = 11.17 pm / V.

[0065] Example 2 Assembly of a triboelectric / piezoelectric hybrid nanogenerator device

[0066] (1) Preparation of patterned PDMS

[0067] PDMS was shaped using an epoxy resin mold with a cylindrical array structure featuring surface depressions. A 10:1 mixture of prepolymer A (mainly poly(dimethyl-methylvinylsiloxane)) and crosslinking agent B (a prepolymer with vinyl side chains) was poured onto the mold surface and cured in a 60°C oven for 6 hours. After demolding, a PDMS film with a micropillar array having a radius of 0.5 mm and a height of 1 mm was obtained, with a distance of 1 mm between each micropillar.

[0068] (2) Fabrication of Zn-Carbide-based triboelectric / piezoelectric hybrid nanogenerators

[0069] A triboelectric hybrid nanogenerator was fabricated based on Zn-Car piezoelectric particles and patterned PDMS, using 3 mm thick particles with an area of ​​2 × 2 cm². 2 Patterned PDMS with a micropillar array serves as the top triboelectric layer, with a thickness of 3 mm and an area of ​​2 × 2 cm. 2A PDMS film was used as the bottom dielectric layer. A 2mm wide and 1mm thick double-sided adhesive tape was attached to the edge of the PDMS surface as a spacer. 20mg of Zn-Car powder was loaded between the two PDMS layers as a piezoelectric layer. Aluminum foil and copper tape were added to the back of the two PDMS layers as electrodes. The outermost layer was encapsulated with polyimide tape, resulting in a Zn-Car triboelectric / piezoelectric hybrid nanogenerator device with sealing and waterproof properties.

[0070] like Figure 9 As shown, this is a PDMS film with a micropillar array of 0.5 mm radius and 1 mm height, manufactured by a template-assisted method in Example 2. The distance between each micropillar is 1 mm.

[0071] like Figure 10 As shown, this demonstrates the flexibility of the Zn-Car_TPHG device fabricated using patterned PDMS in Example 2. Since PDMS is a flexible material, the TPHG fabricated from flexible PDMS exhibits good flexibility, with excellent compression and bending properties, making it suitable for use in flexible wearable devices.

[0072] like Figure 11 As shown, the open-circuit voltage of Zn-Car_TPHG constructed using patterned PDMS and unpatterned PDMS in Example 2 is shown, where 2×2cm 2 The open-circuit voltage of the Zn-Car TPHG constructed with patterned PDMS is about 1.5 times that of the unpatterned one at the same pressure, indicating that patterned PDMS can improve the output performance of the TPHG device.

[0073] like Figure 12 The image shows the piezoelectric properties of the TPHG devices in Example 2 with 2:1 Zn-Car MOF and 1:1 Zn-Car MOF added. 5 mg / cm³ of Zn-Car MOF was added. 2 The maximum open-circuit voltage of the 2:1Zn-Car_MOF TPHG device is 37.9V, which is less than the voltage of the device with 5mg / cm³ added. 2 The 47.1V TPHG device of 1:1Zn-Car_MOF indicates that 1:1Zn-Car_MOF has better piezoelectric performance than 2:1Zn-Car_MOF.

[0074] like Figure 13 and Figure 14The figure shows the output voltage, output current, and output power density of the 1:1 Zn-Car_TPHG device in Example 2 under different external load conditions. The output voltage of the Zn-Car_TPHG increases from 0.1V to approximately 39.5V with increasing external load, while the output current decreases from 0.36μA to 0.012μA, and a power density of 0.533μW / cm² is achieved with a 150MΩ load resistance. 2 Maximum output power density.

[0075] like Figure 15 The figure shows the open-circuit voltage of the 1:1 Zn-Car_TPHG device in Example 2 under different pressure conditions. At 1 kPa, the Zn-Car_TPHG device still has an open-circuit voltage of 15.2V, and at 100 kPa, the open-circuit voltage reaches 131V, demonstrating that the Zn-Car_TPHG device has a wide detection range and can withstand significant pressures such as those from the movement of electric vehicle wheels.

[0076] like Figure 16 The figure shows the cycle stability of the 1:1 Zn-Car_TPHG device in Example 2. The Zn-Car_TPHG device maintained a stable open-circuit voltage during 9000 contact-to-disconnect cycles at a frequency of 1 Hz, and the signal did not show significant drift or fluctuation, confirming the structural integrity and mechanical stability of the Zn-Car_TPHG device for long-term use.

[0077] like Figure 17 As shown, this is the 2×2cm used in Example 2. 2 A schematic diagram of a 1:1 Zn-Car TPHG device constructed using patterned PDMS harvesting raindrop energy and a test graph showing the charging of a 1μF capacitor. Water droplets fell at a rate of 60 μL / drop from a height of 20 cm at a frequency of 1.5 Hz. The voltage-time relationship in the capacitor charging curve demonstrates that rainwater can stably and effectively charge the capacitor via the TPHG.

[0078] like Figure 18 As shown, this is a 2×2cm example from Example 2. 2 The open-circuit voltage of the Zn-Car_TPHG for tidal energy harvesting. In a simulated tidal environment on a beach, the Zn-Car_TPHG achieves an output voltage of approximately 0.65V, demonstrating that the Zn-Car_TPHG device can be used to harvest ocean tidal energy.

[0079] like Figure 19 As shown, this is a 10×10cm sample from Example 2. 2 Open-circuit voltage of Zn-Car_TPHG at different speeds of the electric vehicle. At an average speed of 5 km / h...-1 At that time, Zn-Car_TPHG achieved an open-circuit voltage of 67.4V at 25km·h. -1 An open-circuit voltage of 121V was obtained, proving that the Zn-Car_TPHG device has the function of monitoring the speed of electric vehicles and harvesting driving energy when installed on the road.

[0080] like Figure 20 As shown, this is an example of using 2×2cm in Embodiment 2 of the present invention. 2 The Zn-Car_TPHG sensor is placed on the heel of the insole to collect output signal images for various motion states. The signal strength and waveform of the Zn-Car_TPHG output are not completely identical under different motion states (walking, tiptoeing, running, jumping), indicating that the Zn-Car_TPHG can effectively monitor various movements and distinguish different human motion states.

[0081] like Figure 21 As shown, this is an example of using 2×2cm in Embodiment 2 of the present invention. 2 The Zn-Car_TPHG, placed on the heel of the insole, collects waveform signals from the human body during walking. Typically, the gait cycle comprises four phases: heel contact, toe contact, heel departure, and toe departure. As the user walks forward, two negative peaks (1, 2) representing heel and toe contact are observed, followed by two positive peaks (3, 4) representing heel and toe departure. Furthermore, the output voltage of the Zn-Car_TPHG can be further refined by extracting several characteristics, such as the shape, amplitude, and time interval between adjacent cycles, to distinguish detailed motor physiological information. This demonstrates its advanced capabilities in monitoring human posture and gait, and its potential application in the prevention of gait-related diseases.

[0082] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A triboelectric / piezoelectric hybrid nanogenerator device, characterized in that, Peptide-based biometal-organic framework piezoelectric materials are added to patterned PDMS to construct triboelectric / piezoelectric hybrid nanogenerator devices; The synthesis method of the peptide-based biometal-organic framework piezoelectric material includes: adding zinc nitrate hexahydrate and L-carnosine to a solvent and heating to obtain Zn-Car_MOF material, wherein the molar ratio of zinc nitrate hexahydrate to L-carnosine is 1:

1.

2. The triboelectric / piezoelectric hybrid nanogenerator device according to claim 1, characterized in that, The heating temperature is 80-150 ℃.

3. The triboelectric / piezoelectric hybrid nanogenerator device according to claim 2, characterized in that, The addition amount of the Zn-Car_MOF material meets the following requirement: 0.1 mg / cm³ 2 The amount of Zn-Car-MOF material added is ≤5 mg / cm³ 2 .

4. The triboelectric / piezoelectric hybrid nanogenerator device according to claim 2, characterized in that, In a triboelectric / piezoelectric hybrid nanogenerator device, a peptide-based biometal-organic framework piezoelectric material is added between patterned PDMS and unpatterned PDMS films and separated by tape. The outer layers of both patterned and unpatterned PDMS films are covered with aluminum foil and copper conductive tape as electrodes and encapsulated with a PI film.

5. The application of the triboelectric / piezoelectric hybrid nanogenerator device according to any one of claims 1-4 in environmental energy harvesting and gait monitoring.

Citation Information

Patent Citations

  • Metal organic framework material as well as ligand and application thereof

    CN116425997A